Cashless transactions through ecommerce platform in the Post-Covid-19 - Ab. Rahman, Hamidah; Hassan, Razali (PKP, 2020)
COVID-19 pandemic becomes one of the critical challenges that occur around the world that is impressed by the social environment of society. This paper is based on a literature review of the conceptual framework of cashless transactions based on attitude customized in e-commerce usage in post-COVID-19. The main purpose of this study paper is to formulate elements that are suitable for the proposed cashless transactions model based on attitude tailored to the use of e-commerce in post-COVID-19 to enhance trustworthiness value and best practices among consumers. The conceptual framework of cashless transactions based on attitude through e-commerce focuses on the influence of e-commerce usage features, perceived behavioural control (consumer abilities), and subjective norms related to motivational values influenced by the social environment. This research paper was also carried out based on previous studies and the use of Theory Of Planned Behaviour tailored to the conceptual framework of the study to be produced. This study proposes a cashless transactions model based on attitude primarily among consumers of higher education institutions. Based on the studies, focuses on the culture of using cashless transactions specializing in e-commerce platforms that will guide further studies in the future.